Utilization of clay materials as support for aspergillus japonicus lipase: An eco-friendly approach - Remonatto, Daniela [UNESP]; Ferrari, Bárbara Ribeiro [UNESP]; Bassan, Juliana Cristina [UNESP]; Mussagy, Cassamo Ussemane [UNESP]; Santos-Ebinuma, Valéria de Carvalho [UNESP]; de Paula, Ariela Veloso [UNESP] (MDPI, 2021)
Lipase is an important group of biocatalysts, which combines versatility and specificity, and can catalyze several reactions when applied in a high amount of industrial processes. In this study, the lipase produced by Aspergillus japonicus under submerged cultivation, was immobilized by physical adsorption, using clay supports, namely, diatomite, vermiculite, montmorillonite KSF (MKSF) and kaolinite. Besides, the immobilized and free enzyme was characterized, regarding pH, temperature and kinetic parameters. The most promising clay support was MKSF that pre-sented 69.47% immobilization yield and hydrolytic activity higher than the other conditions studied (270.7 U g−1). The derivative produced with MKSF showed high stability at pH and temperature, keeping 100% of its activity throughout 12 h of incubation in the pH ranges between 4.0 and 9.0 and at a temperature from 30 to 50◦ C. In addition, the immobilized lipase on MKSF support showed an improvement in the catalytic performance. The study shows the potential of using clays as support to immobilized lipolytic enzymes by adsorption method, which is a simple and cost-effective process.
Keywords: Aspergillus japonicus; Immobilization; Lipase; Montmorillonite KSF